Trends in adolescent motherhood and fertility and related inequalities in the Caribbean 1990-2010 - Nam, Valerie E. (ECLAC, 2016)
The study is a purely descriptive analysis of the trends in adolescent fertility and an assessment of reproductive inequalities in a defined area of the Caribbean region, over the twenty year period 1990-2010 The main data sources used are the decennial censuses of population and housing, the system of vital registration and relevant specialised surveys. The core data for the analysis are stored in the MATERNILAC database maintained by CELADE, the Population Division of ECLAC. The analysis shows that the area has experienced declines in the adolescent birth rate, to varying degrees over the period. Occurring simultaneously with these reductions there were also declines in motherhood among adolescents. The limited data indicating inequalities show overall an association between the declining reductions and education, residence and socio-economic status.